Determination of the Optimum Rates for N, P, and K Fertilizer for Upland Rice Variety “IPB 9G” - Adi, Defiyanto Djami; Lubis, Iskandar; Suwarto, Suwarto; Sugiyanta, Sugiyanta (Department of Agronomy and Horticulture, IPB University, 2019)
A study was conducted to determine the optimum rates of N, P, K fertilizers on “IPB 9G” upland rice variety from March to July 2018 at the Sawah Baru Experimental Field of IPB University, West Java, Indonesia. Three paralel experiments were carried out in a randomized complete block design to test five fertilizing levels, i.e. 0, 50, 100, 150 and 200% of the reference rate. The reference rates of fertilizer application are 100% N = 200 kg Urea ha-1, 100% P = 100 kg SP36 ha-1, and 100% K = 100 kg KCl ha-1. The applied fertilizers were Urea (46% N), SP36 (36% P2O5) and KCl (60% K2O). Fertilizers were applied three times, 40% at planting, 30% at 4 WAP and the rest 30% at 8 WAP; 100% P and 100% K were applied at planting. Increasing N fertilizer from 0 to 200% of the reference rate increased plant height, dry weight biomass at heading and at harvest, number of productive tillers, harvest index, and grain weight per clump. P increased dry weight of the above ground biomass, whereas K fertilizer increased the leaf area, canopy dry weight, number of grain per panicle, panicle length, harvest index and grain weight per clump. The optimum rate of N and P were 107.09 kg Urea ha-1 and 63.3 kg P2O5 kg.ha-1, respectively, whereas the optimal rate for K fertilizer for “IPB 9G” could not be determined with this study.